HIV Late Presenters in Asia: Management and Public Health Challenges - Chen Seong Wong; Lyu Wei; Yeon-Sook Kim (AIDS Research and Treatment)
Many individuals are diagnosed with human immunodeficiency virus (HIV) infection at an advanced stage of illness and are considered late presenters. We define late presentation as a CD4 cell count below 350 cells/mm3 at the time of HIV diagnosis, or presenting with an AIDS-defining illness regardless of CD4 count. Across Asia, an estimated 34–72% of people diagnosed with HIV are late presenters. HIV late presenters generally have a higher disease burden and higher comorbidity such as opportunistic infections than those who are diagnosed earlier. They also have a higher mortality rate and generally exhibit poorer immune recovery following combined antiretroviral therapy (cART). As such, late HIV presentation leads to increased resource burden and costs to healthcare systems. HIV late presentation also poses an increased risk of community transmission since the transmission rate from people unaware of their HIV status is approximately 3.5 times higher than that of early presenters. There are several factors which contribute to HIV late presentation. Fear of stigmatisation and discrimination are significant barriers to both testing and accessing treatment. A lack of perceived risk and a lack of knowledge by individuals also contribute to late presentation. Lack of referral for testing by healthcare providers is another identified barrier in China and may extend to other regions across Asia. Effective strategies are still needed to reduce the incidence of late presentation across Asia. Key areas of focus should be increasing community awareness of the risk of HIV, reducing stigma and discrimination in testing, and educating healthcare professionals on the need for early testing and on the most effective ways to engage with people living with HIV. Recent initiatives such as intensified patient adherence support programs and HIV self-testing also have the potential to improve access to testing and reduce late diagnosis.